Effect of background scan on performance of neighbouring channels in 802.11 networks. (19th February 2008) - Singh, Gurpal; Atwal, Ajay Pal Singh; Sohi, B.S.
Background scanning is being employed by IEEE 802.11 mobile nodes for discovering neighbouring access points and their channels without breaking connectivity with the current access point. Information gathered thus, is fed to handoff algorithm for making proactive and fast handoff decisions. Active background scanning though fast generates signalling traffic in the form of management frames. Signalling overhead associated with active scanning can affect the performance of traffic operating on the neighbouring channels which are being actively scanned. Active background scanning though widely used for neighbour discovery, very little efforts have been made to study its effect on performance of traffic on neighbouring channels. In this paper, we have experimentally studied the effect of signalling overhead associated with active background scanning on the performance of traffic on the neighbouring access points. Results have been obtained in the form of packet delay, packet loss, Round Trip Time (RTT) variations in traffic on neighbouring channels due to background scan. Effects of background scan on bulk traffic on the neighbouring channels have also been studied.